Tuesday

October 21, 2014

October 21, 2014

Posted by **Anonymous** on Monday, March 14, 2011 at 4:58pm.

- MATH -
**Anonymous**, Monday, March 14, 2011 at 5:14pm3x/2=(3*2*x)/(2*2)=6x/4

x/4-3x/2=(x/4)-(6x/4)= -5x/4

- MATH -
**Anonymous**, Monday, March 14, 2011 at 5:19pm-5x/4= -1/2 Multiply with 4

-5x= -(1/2)*4

-5x= -2 Divide with -5

x=(-2)/(-5)

x=2/5

x=0.4

- MATH -
**Reiny**, Monday, March 14, 2011 at 5:31pmsimplest way:

x/4 - 3x/2 = -1/2

multiply each term by 4

x - 6x = -2

-5x = -2

x = 2/5

**Answer this Question**

**Related Questions**

Business Math - Using the simplex method, solve the following linear programming...

math - State the null hypothesis, Ho, and the alternative hypothesis, Ha, that ...

math - 9x+5greater than or equal to -40 or 7x+3greater than or equal to -11 ...

Math algebra 1 - Hi I really need help! State any restrictions on the variables...

Math - Objective Function z = 3x - 2y Constraints x > or equal to 1 x < or...

Infinite math - use the M method to solve the following linear programming ...

math - sketch the feasible region for this system of the inqualities and find ...

Math - -13<or equal 3x-8<or equal to -3 -13=3x-8 -5=3x x=-5/3 I hope this...

Math - a/b + b/a = x a/b - b/a = y in the equation above, if a is (not equal) to...

Math - a/b + b/a = x a/b - b/a = y in the equation above, if a is (not equal) to...